An ultra-high power density supercapacitor: Cu(II) phthalocyanine tetrasulfonic acid tetrasodium salt doped polyaniline - Arvas, Melih Besir; Yazar, Sibel; Sahin, Yucel (ELSEVIER SCIENCE SA, 2022)
In this study, an excellent electrode and supercapacitor performance with aqueous electrolyte exhibiting high operating voltage was obtained. Cu(II) phthalocyanine tetrasulfonic acid tetrasodium salt (CuPcTs) was used as a dopant in the polymerization of aniline on carbon felt electrode (CFt) by one-step hydrothermal method. Scanning electron microscopy (SEM) was used to analyze the morphological structure of PANI and CuPcTs doped PANI electrodes. Chemical analysis of the electrodes was performed using X-Ray diffractometry (XRD) and Fourier transform infrared spectroscopy (FT-IR); thermal properties of the electrodes were investigated using thermogravimetric analysis (TG/DTA). The surface area and pore volume of the electrodes were investigated using Brunauer-Emmett-Teller (BET) analysis. The electrochemical properties of the electrodes were investigated using cyclic voltammetry (CV), galvanostatic charge-discharge (GCD) and electrochemical impedance spectroscopy (EIS) methods. With the addition of CuPcTs and the use of graphite plate (GP) as the counter electrode, an asymmetrical supercapacitor was created for pseudocapacitive supercapacitors, in which the properties of redox materials were improved. CuPcTs doped PANI electrode showed a high specific capacitance of 982.2 F g(-1) at 5 mV s(-1) and showed excellent rate capability at different current densities of charge-discharge tests. Furthermore, wide operating-voltage of 3.2 V exhibited an ultra-high energy density value of 12800 W kg(-1) and had an energy density of 764.4 Wh kg(-1). The electrode and supercapacitor displayed retention of capacitance performances of 91.4% and 79.7% after 1000 and 5000 cycles in aqueous electrolyte, respectively. (C) 2022 Elsevier B.V. All rights reserved.
Keywords: High-power density supercapacitor; High-voltage; Phthalocyanine; Aqueous electrolyte; Hydrothermal; Polyaniline; ELECTRODE MATERIAL; CARBON CLOTH; PERFORMANCE; COMPOSITE; GRAPHENE; NANOCOMPOSITE; DEGRADATION; MECHANISMS; AEROGELS; NANOWIRE; Chemistry; Materials Science; Metallurgy & Metallurgical Engineering